Thermal Properties and Electrical Conductivity of Pure In2O3 and Doped with ZrO2 - HANAFI, Z.M.; ISMAIL, F.M.; MOHAMED, A.K.; HAMMAD, F.F. (Asian Journal of Chemistry, 2010)
The thermal properties (TGA, DTA) and AC electrical conductivity of pure In2O3 and ZrO2 doped In2O3 have been studied. The dopants ratio were 1, 3, 5, 8 and 10 mol % of ZrO2. The AC conductivity as a function of temperature was measured in the temperature range 298- 753 K at a frequency 20 KHz. The plots of log σ(Ω-1 cm-1) vs. 1/T (K-1) showed that all curves have three parts and the activation energies for conduction were calculated.